Dispositional Social Comparison Orientation Predicting Multidimensional Social Media Fatigue in Generation Z TikTok Users - Suciani, Galuh; Darmawanti, Ira (Psikostudia : Jurnal Psikologi, 2026)
The rapid expansion of algorithm-based social media platforms has intensified evaluative social interaction among young users, potentially increasing susceptibility to social media fatigue. Individual differences in Social Comparative Orientation are assumed to shape psychological responses to the social media environment. This study aims to examine the role of dispositional Social Comparison Orientation in predicting multidimensional social media fatigue among Generation Z TikTok users. Social Comparative Orientation was measured using the adjusted Iowa-Netherlands Comparative Orientation Measure, while social media fatigue was assessed using a multidimensional scale that included cognitive, emotional, and behavioral fatigue. The data was analyzed using covarians-based Structural Equation Modeling. The findings showed that ability-based comparisons significantly predicted cognitive, emotional, and behavioral fatigue, while opinion-based comparisons showed no significant association. The structural model describes the proportion of small to moderate variance in the fatigue dimension. These findings highlight the comparative tendency of disposition as an intrapersonal vulnerability factor in social media fatigue in an algorithm-mediated social media environment.